Light brightness data near sea turtle nests as measured from the horizon and zenith using a Sky Quality Meter - Shigetomo Hirama; Andrea Sylvia; Tonya Long; Robbin Trindell; Blair Witherington (Data in Brief, 2022)
A Sky Quality Meter (SQM) is a photometer designed to measure night sky brightness. SQMs have been used to interpret light fields for various purposes, including studies of relationships between directional light brightness and sea turtle hatchling orientation. This article reports SQM data collected on a sea turtle nesting beach at Delray Beach, Florida (USA) on 17 August 2020. Three hundred-and-sixty light brightness data were collected by eight consecutive readings in each of the four horizontal directions and the zenith at nine sites. The data also include landward photographic images captured at the nine light-measurement sites. The dataset supports the usefulness of the instrument for biological light-field measurements and refute blanket criticisms on inconsistent measurements that would justify discarding initial readings and averaging over a time series.